Parallel electric field structures associated with the low-frequency oscillations in the auroral plasma - Reddy, R.V.; Singh, S.V.; Lakhina, G.S.; Bharuthram, R. (My University, 2006)
The nonlinear evolution of low-frequency electrostatic oscillations in a magnetized plasma consisting of protons, electrons and oxygen ion beams has been studied. The fluid equations have been used for the oxygen beam, whereas the Boltzmann distributions are used for the protons and electrons. The coupled system of equations are reduced to a single nonlinear differential equation in the rest frame of the propagating wave for any direction of propagation with respect to the ambient magnetic field. This nonlinear differential equation is solved numerically for the parameters charateristic of the auroral acceleration region. Depending on the wave Mach number, proton and oxygen ion concentrations, and driving electric field, the numerical solutions show a range of periodic solutions varying from sinusoidal to sawtooth and highly spiky waveforms. The effects of the plasma parameters, in particular the oxygen ion concentration and the proton temperature on the evolution of the nonlinear waves are examined. The results from the model are compared with satellite observations.
Keywords: Auroral plasma; Electric fields; Low frequency waves; Magnetic field; Nonlinear waves